A computational model of the Cambridge gambling task with applications to substance use disorders. (1st January 2020) - Romeu, Ricardo J.; Haines, Nathaniel; Ahn, Woo-Young; Busemeyer, Jerome R.; Vassileva, Jasmin
Highlights: We developed the first computational model of the Cambridge Gambling Task. As expected, the model showed greater impulsivity for substance-users than controls. The model revealed relationships that were not found using the behavioral measures. Simulated predictions of the model, with fitted parameters, match observed behavior. Abstract: Background: Impulsivity is central to all forms of externalizing psychopathology, including problematic substance use. The Cambridge Gambling task (CGT) is a popular neurocognitive task used to assess impulsivity in both clinical and healthy populations. However, the traditional methods of analysis in the CGT do not fully capture the multiple cognitive mechanisms that give rise to impulsive behavior, which can lead to underpowered and difficult-to-interpret behavioral measures. Objectives: The current study presents the cognitive modeling approach as an alternative to traditional methods and assesses predictive and convergent validity across and between approaches. Methods: We used hierarchical Bayesian modeling to fit a series of cognitive models to data from healthy controls ( N = 124) and individuals with histories of substance use disorders (Heroin: N = 79; Amphetamine: N = 76; Polysubstance: N = 103; final total across groups N = 382). Using Bayesian model comparison, we identified the best fitting model, which was then used to identify differences in cognitive model parameters between groups. Results: The cognitive modeling approach revealed differences in quality of decision making and impulsivity between controls and individuals with substance use disorders that traditional methods alone did not detect. Crucially, convergent validity between traditional measures and cognitive model parameters was strong across all groups. Conclusion: The cognitive modeling approach is a viable method of measuring the latent mechanisms that give rise to choice behavior in the CGT, which allows for stronger statistical inferences and a better understanding of impulsive and risk-seeking behavior.